KONSEP ADMINISTRASI PENDIDIKAN - Meti Fatimah; Ikke Fitriana Nugrahini; Nur Ali Rahmatullah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
The entire set of actions taken to achieve a goal-from organizing to managing everything-is called administration. Exercises such as taking notes, writing letters, and other comparative exercises are undeniably referred to as administration. Every business, office, and organization has an arrangement framework because of this. Where professionals referred to as administrators or administrative staff carry out these responsibilities. The writing of this paper uses a concentration of writing on strategies with the method of gathering information through literature studies obtained from books, and articles in diaries related to the topic and discussion. The term "educational administration" can be used to describe the never-ending process that involves determining and implementing various strategies to provide efficient and effective education. Therefore, "the process of overseeing the acquisition, management, and evaluation of educational materials in educational institutions" is referred to as "educational administration". The phrase "instructional organization" alludes to the most common way of planning substitutes to perform various tasks to fulfill the instructional mission of the ongoing vital drive. The term "educational administration" comes from the combination of the words "administration" and "education", which are the two words that make up educational administration. In other words, educational administration is used in the field of education to enable the achievement of educational goals. This is the main purpose of educational administration.